Instructional Level and Engagement in Students With Behavioral Disorders. - Carr, Chelsea E.; Umbreit, John; Hartzell, Rebecca (Behavioral Disorders, 2022)
This study examined the effects of adjusting the difficulty level of instructional materials on the on-task time and comprehension of four students with emotional and behavioral disorders. All participants previously exhibited low rates of on-task behavior during reading assignments. Students were presented with reading materials at their instructional, frustration, and independent levels to assess the effect on time on-task and comprehension. All four students demonstrated the highest percentage of on-task behavior when presented with reading materials at their instructional level. Comprehension scores were highest for all four students at the independent level and lowest at the frustration level.